2012
DOI: 10.1073/pnas.1121251109
|View full text |Cite
|
Sign up to set email alerts
|

Experience and the developing prefrontal cortex

Abstract: The prefrontal cortex (PFC) receives input from all other cortical regions and functions to plan and direct motor, cognitive, affective, and social behavior across time. It has a prolonged development, which allows the acquisition of complex cognitive abilities through experience but makes it susceptible to factors that can lead to abnormal functioning, which is often manifested in neuropsychiatric disorders. When the PFC is exposed to different environmental events during development, such as sensory stimuli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
321
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(355 citation statements)
references
References 81 publications
(77 reference statements)
10
321
0
8
Order By: Relevance
“…[61][62][63] Although the dynamics of this process may be different in rodents, our observation that GCLM-KO mice present a myelin deficit in the anterior cingulate cortex during peripubertal period and no myelin impairment at adulthood suggests that this latter is a vulnerable time period during which an adequate redox control is required. In agreement with this interpretation, a transcriptomic study in the prefrontal cortex identified genes for which expression profiles specifically peak during late adolescence through early adulthood (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…[61][62][63] Although the dynamics of this process may be different in rodents, our observation that GCLM-KO mice present a myelin deficit in the anterior cingulate cortex during peripubertal period and no myelin impairment at adulthood suggests that this latter is a vulnerable time period during which an adequate redox control is required. In agreement with this interpretation, a transcriptomic study in the prefrontal cortex identified genes for which expression profiles specifically peak during late adolescence through early adulthood (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…Following each sham injury or mTBI(s), the time each rat took to right itself in the recovery cage was recorded as the time‐to‐right . The age range selected for the RmTBIs in rodents represents late‐childhood/early adolescence, while the behavioral outcomes span the adolescent period 21, 22. This time period is particularly important for investigation given the large degree of brain maturation occurring in this time period, specifically in white matter development and functional connectivity, of brain regions like the CC and PFC 23, 24, 25, 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…Thus, possibly, from 6 -8 years we may be tapping in to the shift in prefrontal activation in which the more reactive SS carriers may lag behind their less reactive peers, while at the same time profiting from the more secure strategies in times of distress. Indeed, social experiences throughout the life span influence the development of brain areas involved in selfregulation (see Kolb et al, 2012 for a review). However, such development does not seem to be linear or easy to predict (Ahmed, Bittencourt-Hewitt, & Sebastian, 2015); hence, age effects could be a complex matter.…”
Section: Differential Susceptibility and 5-httlprmentioning
confidence: 99%